Study on the estimate of precipitation with the help of S-band at radar Calcutta - DE, A.C.; BHATTACHARYYA , P.; GHOSH, S. K. (MAUSAM, 1977)
An attempt has been made to study the amount of rainfall associated with the severe cyclonic storm of 14-16 August 1974 with the help of the S-band radar installed at Calcutta. The first two modes of the gray scale, viz. gray and white shades were utilised in this study. It has been found that these modes correspond fairly well with the rates of rainfall recorded at these recording rain gauge stations, and rainfall reported by ordinary rain gauge stations within a radius of 200 km around Calcutta, Isogram analysis of the rates of rainfall at a particular time has also been made and the results compare fairly well with the radar photographs at the corresponding time.